THE DEVELOPMENT OF ISLAMIC EDUCATIONAL THOUGHT IN INDONESIA - Khojir, Khojir; Shalihudin, Ahmad Faishal; Syntha, Nela; Nurhamidah, Winda Islamitha (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The development of educational thought in Indonesia is experiencing quite rapid dynamics. The dynamics of thought cannot be separated from the context of time and its surrounding circumstances. The purpose of writing this article is to examine the dynamics of the development of Islamic educational thought in Indonesia and to analyze the characteristics of educational thought in Indonesia. This research is in the library category with a historical-philosophical approach. Data collection is done by searching the literature in journals, books, research reports, magazines, etc. Analysis of data using content analysis. The research results show that the political situation colors the dynamics of the development of thought in Indonesia, the figures' backgrounds, and socio-culture. The characteristics of educational thought during the pre-independence era were embryonic and focused on dealing with colonialists.